2022
DOI: 10.1371/journal.pone.0265186
|View full text |Cite
|
Sign up to set email alerts
|

High maternal BMI and low maternal blood BDNF may determine the limit of detection of amniotic fluid BDNF throughout gestation: Analysis of mother-fetus trios and literature review

Abstract: Objective An increasing number of studies show the importance of brain-derived neurotrophic factor (BDNF) acting at the feto-placental interface, however, only a few studies describe BDNF levels in amniotic fluid (AF). Methods In this cross-sectional, prospective study, 109 maternal blood-amniotic fluid pairs (including 66 maternal blood-fetal-blood-amniotic fluid trios) were analyzed. BDNF concentrations were measured with a commercially available immunoassay. Results In 71 AF from 109 samples, AF-BDNF co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Furthermore, all three band ratios involving the delta band have moderate positive correlations with maternal BDNF. Our findings also point to the fact that the fetal development may be assisted by the maternal BDNF that reaches the fetal brain through the utero-placental barrier ( Antonakopoulos et al, 2018 ; Flöck et al, 2016 , 2022 ; Kodomari et al, 2009 ), since cord-blood BDNF levels have mainly negligible correlations with RP in the four bands. BDNF plays a crucial role in the modulation of neurogenesis and maturation of neural pathways during neurodevelopment ( Su et al, 2021 ).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Furthermore, all three band ratios involving the delta band have moderate positive correlations with maternal BDNF. Our findings also point to the fact that the fetal development may be assisted by the maternal BDNF that reaches the fetal brain through the utero-placental barrier ( Antonakopoulos et al, 2018 ; Flöck et al, 2016 , 2022 ; Kodomari et al, 2009 ), since cord-blood BDNF levels have mainly negligible correlations with RP in the four bands. BDNF plays a crucial role in the modulation of neurogenesis and maturation of neural pathways during neurodevelopment ( Su et al, 2021 ).…”
Section: Discussionmentioning
confidence: 59%
“…This could be because neurotrophins are transported from the mother into various compartments of the fetal environment such as the amniotic fluid and the placenta ( Cai et al, 2017 ; Flöck et al, 2016 ; Mayeur et al, 2011 ). In a recent study, Flöck et al, (2022) reported that amniotic-fluid BDNF levels have a maternal or placental source ( Flöck et al, 2022 ). Furthermore, they reported that cord-blood BDNF reflects mainly its synthesis by the fetus ( Flöck et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Even the evaluation of amniotic fluid levels of neurotrophins is not, however, entirely free of bias as Flock et al reported that high maternal BMI and low maternal blood BDNF may differentiate the limit of detection of amniotic fluid BDNF throughout gestation. 17 Possibly the best way to observe potential differences among growth restricted and AGA fetuses is to review cord blood levels of neurotrophins. To date, this has been investigated only in term pregnancies by Briana et al in pregnancies complicated by gestational diabetes mellitus with the authors mentioning the absence of a specific correlation with fetal growth percentiles.…”
Section: Resultsmentioning
confidence: 99%